(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The oppressive culture based on neo-fascist and dystopian discourse aggravates the current humanitarian situation of refugees, as they are excluded, marginalized and disrespected by the receiving nation. Given this, the article intends to emphasize the need for the struggle for recognition, the confrontation of fascist and dystopian discourses, for a (re) identity construction of refugees, liberating, almost naturally, without oppression and prejudice, as mechanisms for transformation. cultural and legislative Effective respect for the refugee requires the transformation of current human behavior based on international law and the constitutional principles of equality, difference and human dignity. The present research is relevant to the academic and social environment, considering that migrations, and especially forced migrations, are in vogue in today’s complex society. Through the deductive methodology, using the technique of bibliographical research, aims to indicate the paths and paths of refugees in the current square history, pointing to the recognition of difference as a difficult but necessary task, to better navigate today’s turbulence. Millions of people are forced to leave their homes, families, dreams for protection, dignity, respect, freedom and better living conditions. From this perspective, this phenomenon is latent and Brazil is also one of the destination countries of many refugees. So essential is to think, write and talk about the topic. It is necessary that the laws and the Brazilian society are prepared for the receptivity, to make them part, friends and not enemies, transforming an apparent problem in a “celebration” of the plurality and cultural diversity, miscegenation that is already characteristic of Brazil, and the subjective, individual and collective internalization of human rights, in a process of recognition and alterity towards the other. To investigate the complex re (construction) of the identity of forced migrants, in the light of an equality that respects the difference of refugees in Brazil, taking into account the emergence of “new discourses” that revisit fascism, enhancing humanitarian issues.